(untitled) (SCIENCE TIME JOURNAL, 2026)
This article provides a scientific analysis of the role of innovative pedagogical technologies in shaping learning motivation among medical students. The study examines the essence of learning motivation, the factors influencing it, and the importance of modern teaching approaches. In particular, the roles of interactive methods, problem-based learning (PBL), simulation-based education, and digital technologies in enhancing student engagement, independent thinking, and professional competencies are analyzed. The article also highlights the positive impact of these technologies on the educational process, their effectiveness in increasing motivation, and their practical applications. The findings indicate that the effective implementation of innovative pedagogical technologies is a key factor in improving the quality of medical education and training highly qualified healthcare professionals.